Games and gamers: the influence of participating players on the process and outcome of regional spatial energy games - Hartmut Dumke; Pia Nabielek (Energy, Sustainability and Society)
Abstract Background One major question of climate and energy policy is how to act under conditions of great uncertainty. This contribution relates to the literature that studies how various actors draft regional energy scenarios and pathways in so-called serious games. Serious gaming aims to foster contextual knowledge generation about complex problems and spatial solutions associated with sustainability transitions. Little attention has thus far been paid to the question of how to design a serious game that enables desired game results through different player constellations. Shortcomings in the literature regarding the inclusion of relevant players and secure game experience through player interaction are covered by stakeholder theory. Our approach assigns different attributes to individual players which secures that the game is played from various perspectives and by actual stakeholders. Results and conclusions Our empirical study shows the impact of players with different stakeholder attributes on two game results: the first game result is a spatial energy scenario (output) and the second result is the collective and place-based learning experience during the game (outcome). The paper closes with three concluding recommendations: It is important to pay attention to player’s attributes as well as to constellations of players since they influence game experience (outcome) and achieved scenario (output). Player’s attributes and constellations can partly explain differences in game results, but more empirical work on the influence of players and games on the results is necessary. In the future, more attention should be paid to the interaction, discussions and dynamics within the player teams. The optimization of player teams needs to be strongly considered in game design. Also, we note that if the game is played in a regional context, the spatial orientation (the region) could be taken into greater account when applying stakeholder theory.